The Behaviorally Based Intervention Approach to Improve Self-Efficacy of Students' with Attention Deficit Hyperactive Disorder in Elementary School - Abdul Sholeh; Asep Supena; Ahmad Arifuddin (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
AbstractThis research is motivated by the low self-efficacy of elementary school students with Attention Deficit Hyperactivity Disorder (ADHD) that impact on their academic failure. This study aims to describe the behaviorally based intervention approach in improving the self-efficacy of ADHD students in elementary school. This case study involved five students of an elementary school in Cirebon city. The data were gathered via observations, interviews, and documentation and then analyzed using the descriptive qualitative technique. Â The results showed that the use of a behavior-based intervention approach could enhance the students' self-efficacy in the aspects of academic achievement, adjustment, social relations, and self-assessment. Therefore, the behavior-based intervention approach can be used as an alternative in increasing the self-efficacy of students with ADHD.Keywords: behaviorally based intervention approach, self-efficacy, attention deficit hyperactivity disorder.Â AbstrakPenelitian ini dilatarbelakangi oleh rendahnya efikasi diri siswa sekolah dasar dengan Attention Deficit Hyperactivity Disorder (ADHD) yang berdampak pada kegagalan akademik mereka. Penelitian ini bertujuan untuk mendeskripsikan pendekatan intervensi berbasis perilaku dalam meningkatkan efikasi diri siswa ADHD di sekolah dasar. Studi kasus ini melibatkan 5 siswa sekolah dasar di kota Cirebon. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dan kemudian dianalisis dengan teknik analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa penggunaan pendekatan intervensi berbasis perilaku dapat meningkatkan efikasi diri siswa, baik pada aspek prestasi akademik, aspek penyesuaian diri, aspek hubungan sosial, maupun aspek penilaian diri. Untuk itu, pendekatan intervensi berbasis perilaku dapat menjadi alternatif dalam meningkatkan efikasi diri siswa ADHD.Kata kunci: pendekatan intervensi berbasis perilaku, efikasi diri, attention deficit hyperactivity disorder.